How do institutional investors approach disposition effect in crises - Heimann, Valentina Iris Maria (2021)
This work project investigates how institutional investors cope with the disposition effect in crisis and non-crisis environments. Specifically, the internal and external idiosyncratic characteristics of institutional investors are used to find reasons for differences in the magnitudes of factors aggravating disposition effect. The study lays the foundation for easy-to-implement countermeasures against the disposition effect. This is achieved by consolidating countermeasures used by institutional investors in crisis and non-crisis environments into the self-developed SAFE(R) framework and by proposing action points for each investor group to overcome their specific obstacles that cause an increase in disposition effect.